The Effect of Organic Fertilizing on Changes In Chemical Properties and Growth of Passage Plants (Brassica juncea) on Psamment Soil - Elizabeth Kaya; Simson Liubana; Delvi Polnaya (Agrologia, 2022)
Soil quality indicates the ability of the soil to perform its functions in land use or ecosystems. The aim of the study was to determine the effect of liquid organic fertilizer and sago ella compost on available NPK, NPK uptake and growth of mustard (Brassica Juncea) in Psament soil. This research was conducted in the laboratory and in the Greenhouse. The experiment used compost fertilizer at doses of 0.10, and 20 tons/ha, and liquid organic fertilizer with doses of 3 ppm and 6 ppm. The results of the study found that the application of compost had a significant effect on P-available, available K and plant height, liquid organic fertilizer had a significant effect on P-available, soil pH, N uptake. The interaction between the two had an effect on P and K uptake and the number of leaves had no significant effect.